Ecologia floral de Bauhinia forficata link: interações ecológicas na restauração de ecossistemas - Capitani, Luana Camila (2016)
This study aimed to determine the details of the offer and quality of floral resources in Bauhinia forficata Link, native species of Seasonal Deciduous Forest in Rio Grande do Sul, and how they influence the attraction and interaction with the flower visitors and other plant species. It sought to further determine the ecological mechanisms that are established from the plant interactions / animal that can be used as a theoretical basis for the creation of ecological restoration strategies. The work was conducted in the municipality of Santa Maria, central region of Rio Grande do Sul. Were selected 11 matrices based on the environmental quality of the fragments their surroundings and morphophysiological and phytosanitary characteristics of individuals, of which was evaluates the phenology, volume and concentration of nectar instanding crop (NID), pollinic viability, suitability for autogamy, floristic diversity of the surrounding areas, diversity, intensity and behavior of diurnal and nocturnal flower visitors and ditrophic networks of plant-pollinator interaction. The variables were tested by comparison of means, Principal Component Analysis (PCA) and correlation analysis. The average volume of NID observed for the species was 40.3 μl and the mean concentration was 0.265 mg / μl. The average pollen viability was 81.43%, and the species has proved unfit to autogamy. The average number of floral visitors was 18.24 per matrices and the average intensity of interaction was 59.94%. Were accounted for 730 floral visitors belonging to 29 morphospecies, 657 at the diurnal monitoring and 73 at nocturnal monitoring. The main order observed was Lepidoptera. The suborder Rhopalocera was the most abundant between diurnal visitors (30.43%), and the suborder Heterocera the most abundant among the nocturnal visitors (50%). Proved to be effective pollinators of Bauhinia forficata the bumblebee (Hymenoptera) morphospecies, gray-moth (Pyrgus sp.) (Lepidoptera: Heperiidae) and orange-black-butterfly (Helyconius sp.) (Lepidoptera: Nymphalidae). The functionally effective pollination systems for Bauhinia forficata in the study area are the Psychophily (butterflies) and Melittophily (bumblebees). In the analysis of floristic diversity were found 34 species, the Shannon diversity index ranged between 1.46 and 2.43 between plots. The Bauhinia forficata species, Acacia velutina and Strychnos brasiliensis have the greatest relative densities, respectively, 10.97%, 10.42% and 8.78%. It can be concluded that both the supply and quality of resources influence at the attraction of visitors, as the interaction of visitors with flowers interfered at the availability of resources. The quantity, quality and plasticity of the offered floral resources, the generalist attraction of visitors, the time and intensity of flowering, the inability to autogamy and geitonogamy, high rates of pollen viability and the high degree of connectance of ditróficas webs, are responsible for initiate important ecological mechanisms between this and other ecosystem agents, being them: compensation mechanisms, of species coexistence, induction of gene flow and competition and partilhamento of the resources. These results demonstrate that Bauhinia forficata is an important energy source for the diet of a wide range of pollinators and acts as an inducer of ecological processes and gene flow in the study area.